Gamma-glutamyltransferase-associated glycoprotein patterns in human seminal plasma of normozoospermic men: a new aspect of biomarker heterogeneity - Jankovic, Tamara; Danilovic Lukovic, Jelena; Goc, Sanja; Mitic, Ninoslav; Hajdukovic, Ljiljana; Jankovic, Miroslava (Biomedical papers, 2024)
Background. Gamma-glutamyltransferase (GGT) is a well-known laboratory biomarker. In spite of high concentration and the possible biomedical importance of estimating GGT in human seminal plasma (hSP), it has not been widely explored in reproductive physiology. This study aimed to complement existing data on its diversity, previously obtained on seminal extracellular vesicles, by analyzing matched soluble fraction of hSP. The GGT-associated patterns of selected glycoproteins were analyzed in order to establish an adjunct referent parameter for differentiation between known high molecular mass forms of GGT. Getting insight into distinct GGT-associated glycoprotein patterns should contribute to define them together as possible multimarkers. Methods. GGT forms in soluble, membrane-free-fraction isolated form hSP of normozoospermic men were analyzed using gel filtration and lectin blotting using WGA (wheat germ agglutinin) and Con A (concanavalin A). Results. Widely distributed GGT (with two to three partially resolved peaks), which may correspond to high molecular mass aggregates, were detected. GGT-associated patterns of selected glycoproteins (at position of big, medium, and small-GGT) all comprised high molecular mass WGA-reactive smears, but differed in the presence of Con A-reactive glycans, as well as mucin-associated antigens CA19-9 and CA125. Conclusions. GGT contributes to several molecular patterns that differ between the soluble and extracellular vesicle fractions of hSP. Their glycobiochemical heterogeneity is due to difference in the presence of distinct sialylated and mannosylated glycans. Moreover, GGT-associated glycoprotein patterns differentiate between high molecular mass forms of GGT in the soluble fraction of hSP. They hold promise as possible targets for increasing biomarker potential of GGT.
Keywords: human seminal plasma; gamma-glutamyltransferase; sialylated glycans; CA19-9; CA125